The impact on firm performance: evidence from CEO education - Silvina Silvina; Robin Robin; Wisnu Yuwono (Faculty of Economics and Business Mulawarman University, 2022)
The purpose of this paper is to examine the impact of CEO Education on Firm Performance. The sample covers 180 observations from IDX LQ45 listed on Indonesia Stock Exchange for period 2017 until 2020. The CEO Education is defined by the field of study in economic, management, business, or accounting. Firm Performance is measured by Tobin’s Q from market based perspective. Board characteristics and Stock Returns are used as control variables in this paper. The result shows that there’s a relationship between CEO Education and Firm Performance. CEO with economic, management, business, or accounting background have a positive and significant impacts on Firm Performance. The result becomes stronger with additional test of CEO Education measured by the level and quality of education on Firm Performance, supporting that CEO Education does enchance the Firm Performance.